Produksi Bioethanol Berbasis Nira Sorgum Manis (Sorghum Bicolor) Melalui Rekayasa Bioproses Pada Kultivasi Batch dan Destilasi Satu Tahap - Grace Ananda; M Saleh; Rosalia Sira Sarungallo (Prodi Teknik Kimia, 2023)
The purpose of this research in general is to obtain a productive and efficient bioethanol production process technology through bioethanol production engineering of the Sweet sorghum Nira (Sorghum bicolor) using Saccharomyces cerevisiae in Batch cultivation. This research is specifically aimed at; Determining the concentration of sugar and bioethanol at the end of fermentation to nira sorghum sweetened with presses and extraction; Determinethe optimization of the column height (the volume Destilat) bioethanol distillation tool against the yield and rendament. Nira Sweet Sorghum (Sorghum bicolor) potentially as the raw material ofbioethanol production. In this study the varieties used were sweet Sorghum Super 1, with a brix sugar content of 6% through the stage of pressing of the sorghum stem and 3% through the extraction stage of the sorghum rod. The level of bioethanol obtained after fermentation is 19% in the pressing process and 10% in the extraction process. Based on the results of studies that have been done in this study, it can be concluded that: the highest bioethanol summation is the result of distillation by using a column height of 44 cm (ordinary distillation apparatus) of 75% of the pressing result. The highest bioethanol rendament is 0.722% by using a column height of 44cm (ordinary destillation). Bioethanol Yield is 4.3% by using a column height of 44cm (ordinary destillation)